Ameliorative Effects of Acanthopanax trifoliatus on Cognitive and Emotional Deficits in Olfactory Bulbectomized Mice: An Animal Model of Depression and Cognitive Deficits. (21st March 2013) - Sithisarn, Pongtip; Rojsanga, Piyanuch; Jarikasem, Siripen; Tanaka, Ken; Matsumoto, Kinzo
Abstract : Acanthopanax trifoliatus is a plant that has been traditionally used in Thailand as a vegetable and a tonic. This study investigated effects of the aqueous extract of its leaves (ATL) on cognitive and emotional deficits using an olfactory bulbectomized mouse (OBX) model. OBX mice were treated daily with ATL (250 and 500 mg/kg, p.o.) 3 days after OBX. Antidementia drug tacrine (2.5 mg/kg/day) and antidepressant drug imipramine (10 mg/kg/day) were given i.p. as reference drugs. OBX significantly impaired cognitive behavior in a novel object recognition test and a modified Y-maze test and induced depression-like behavior in a tail suspension test. ATL and tacrine treatment attenuated OBX-induced cognitive deficits, whereas ATL and imipramine improved OBX-induced depression-like behavior. Neurochemical studies conducted after completing behavioral experiments demonstrated that OBX downregulated the expression levels of cholinergic marker genes encoding choline acetyltransferase and muscarinic M1 receptor in a manner reversed by ATL and tacrine. Moreover, ATL and tacrine administration inhibited the ex vivo activity of acetylcholinesterase in the brain. These findings suggest that ATL is beneficial for the treatment of cognitive and emotional deficits related to dementia with depressive symptoms and that the antidementia effect of ATL is mediated by normalizing the function of central cholinergic systems.